2014
DOI: 10.2174/157339631130900007
|View full text |Cite
|
Sign up to set email alerts
|

Nonalcoholic Fatty Liver Disease In Children: Recent Practice Guidelines, Where Do They Take Us?

Abstract: Nonalcoholic fatty liver disease (NAFLD) is the most common cause of chronic liver disease in children and adolescents in the United States. It is strongly associated with childhood obesity, insulin resistance and metabolic syndrome. Although some children with NAFLD may remain asymptomatic, progression to nonalcoholic steatohepatitis (NASH), and to advanced stages of fibrosis and cirrhosis is well recognized. Unfortunately, despite the increase in awareness of this disease, there are still no reliable non-inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 0 publications
0
13
0
Order By: Relevance
“…According to a previous report, some children with non-alcoholic fatty liver disease are at risk for developing nonalcoholic steatohepatitis [25]. Although there is a difference in clinical conditions between fatty liver caused by starvation and that by obesity, a similar pathogenetic mechanism is hypothesized [24].…”
Section: Discussionmentioning
confidence: 99%
“…According to a previous report, some children with non-alcoholic fatty liver disease are at risk for developing nonalcoholic steatohepatitis [25]. Although there is a difference in clinical conditions between fatty liver caused by starvation and that by obesity, a similar pathogenetic mechanism is hypothesized [24].…”
Section: Discussionmentioning
confidence: 99%
“…Nonalcoholic fatty liver disease (NAFLD) is the hepatic manifestation of the obesity and metabolic syndrome epidemics and now affects up to 45% of adults and 10% of children in the United States . Nonalcoholic steatohepatitis (NASH) is the aggressive form of NAFLD that can progress to cirrhosis and end‐stage liver disease requiring liver transplantation (LT) . Recent adult data have shown that NASH is the third most common indication for LT in the United States and is expected to become the leading indication over the next 1–2 decades .…”
Section: Introductionmentioning
confidence: 99%
“…NAFLD represents a disease spectrum that ranges from simple steatosis to non-alcoholic steatohepatitis (NASH), to advanced fibrosis and ultimately cirrhosis [24]. The presence and stage of fibrosis is considered an important factor in the prognosis of NAFLD and the prediction of the risk of developing cirrhosis [25].…”
Section: Discussionmentioning
confidence: 99%